Disaster Management in Banjarmasin Through Communication Optimization - Yuliarti, Astinana; Kumalawati, Rosalina; Anggraini, Rizky Nurita (Jurnal Geografika (Geografi Lingkungan Lahan Basah), 2023)
Disaster communication is a process of creating, sending, and receiving messages from one or more people, which can be done directly or through the media, in various disaster contexts such as pre-disaster, when a disaster occurs, and post-disaster and generates responses or feedback. The role of disaster communication in conveying information is very important amidst technological advances in helping people reach information. This research aims to determine the extent of the disaster communication process carried out by the Banjarmasin City of Regional Disaster Management Agency/Badan Penganggulangan Bencana Daerah (BPBD) in conveying information and educating the public regarding disasters. This research uses a qualitative descriptive approach. The results of the research show that in the process of conveying information to the BPBD of the Banjarmasin community, most of them have carried out their activities quite well, such as Customer Focus, Situational Awareness, and Leadership Commitment, while two other indicators, namely Media Partnership and Soft and Hard Power, are not yet running so they need attention. specifically, such as the process of conveying information via social media still using reporting language rather than journalistic language rules, as well as the limited human resources needed to manage information related to disaster prevention and management before it is conveyed to the wider community.